PARASITE FAUNA OF PARANTHIAS COLONUS (VALENCIENNES, 1846) FROM ELSARGENTO, BAJA CALIFORNIA SUR, MEXICO - Mendoza Cruz, Margarita (2013)
Paranthias colonus(Valenciennes, 1846) is used as fish bait replacing first class fish that have been overfished in the Gulf of California. Due to its recent commercial importance, the parasite fauna of P. colonusfrom of El Sargento, Baja California Sur, Mexico is characterized to define its role in the life cycle of its parasites. 30 fishes were fixed in 4% formaldehyde for later examination. Helminths and copepods were treated with conventional techniques specific to each kind of parasite. P. colonushad 100% prevalence and 46.5 mean intensity of parasites. Adults of Pseudorhabdosynochus sp., Prodistomum orientalis, Brachyphallus sp., Lecithochirium sp., Spinitectus sp., Caligus sp., Pandaridae, and Hatschekia sp. and larevae of Tetragonocephalidae, Scolex pleuronectis and Anisakis sp. were found. There was evidence of host specificity of Pseudorhabdosynochussp. and Hatschekiasp. by serranid fish. P. orientalisis reported for the second time. Hemiuridae are generalists so Paranthiashas added to this host range. The presence of the metacestodes S. pleuronectisand Tetragonocephalidae indicates their role in Paranthiasas intermediate or paratenic hosts because they are found in adult elasmobranches. Anisakissp. and Caligussp. are of wide geographic distribution and host range. Anisakissp. is the only worm that poses a potential danger to public health because it causes anisakidosis. Members of the family Pandaridae are almost exclusive parasites in elasmobranchians and Paranthiasis widely spread in its hosts. This work reports the first world record of hosts and localities of the studied materials.